2022
DOI: 10.1177/0306624x221113530
|View full text |Cite
|
Sign up to set email alerts
|

The Prison Rape Elimination Act (PREA): Snitching, Sexuality, and Normalizing Deviance

Abstract: The normalization of deviance in the form of prison rape finds common themes in media, rape myths, and common discourse. However, these portrayals fail to include real world policies and the perspectives of incarcerated populations. As such, the normalization of deviance is assessed in the context of the implementation of the Prison Rape Elimination Act (PREA). A thematic analysis was conducted using qualitative survey responses from 407 males incarcerated in three medium-level security state prisons in the So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The few studies analyzing survey data on perceived safety and/or PREA attitudes among justice-involved persons tend to confine the evaluation to staff and/or administrator responses (Hensley et al, 2002;Hensley and Tewsbury, 2005;Moster and Jeglic, 2009;Rudes et al, 2021), data collected before the enactment of PREA (Struckman-Johnson et al, 2013;Tewksbury, 1989), or qualitative themes rather than empirical predictors (Smith and Dunton, 2022). According to the findings from this limited pool of research, wardens appear somewhat open to prison reform policies (Moster and Jeglic, 2009), staff perceive PREA as an administrative barrier (Rudes et al, 2021), incarcerated residents see value in effective risk assessments, better classification strategies, and quality safety programs (Smith and Dunton, 2022;Struckman-Johnson et al, 2013), and some physical attributes are related to fear of sexual assault (Tewksbury, 1989) and awareness of sexual coercion (Worley et al, 2010) in prison. While each of these studies contribute meaningfully to contemporary knowledge of the topic, none empirically assess predictors of perceived safety among prison residents since the inauguration of PREA.…”
mentioning
confidence: 99%
“…The few studies analyzing survey data on perceived safety and/or PREA attitudes among justice-involved persons tend to confine the evaluation to staff and/or administrator responses (Hensley et al, 2002;Hensley and Tewsbury, 2005;Moster and Jeglic, 2009;Rudes et al, 2021), data collected before the enactment of PREA (Struckman-Johnson et al, 2013;Tewksbury, 1989), or qualitative themes rather than empirical predictors (Smith and Dunton, 2022). According to the findings from this limited pool of research, wardens appear somewhat open to prison reform policies (Moster and Jeglic, 2009), staff perceive PREA as an administrative barrier (Rudes et al, 2021), incarcerated residents see value in effective risk assessments, better classification strategies, and quality safety programs (Smith and Dunton, 2022;Struckman-Johnson et al, 2013), and some physical attributes are related to fear of sexual assault (Tewksbury, 1989) and awareness of sexual coercion (Worley et al, 2010) in prison. While each of these studies contribute meaningfully to contemporary knowledge of the topic, none empirically assess predictors of perceived safety among prison residents since the inauguration of PREA.…”
mentioning
confidence: 99%
“…Fowler et al's research (2010) indicated that new prisoners were more likely to self-report sexual victimisation; perhaps because of newly implemented reporting initiatives, or because they were less impacted by traditional views about ‘snitching’. Smith and Dunton (2022) concurred that prisoners in the southern states of the United States supported institutional prison mechanisms that reduced risks of prison rape and endorsed the view that reporting rape was widely supported among prisoners.…”
Section: The Prison Contextmentioning
confidence: 86%